2016
DOI: 10.18203/2394-6040.ijcmph20163390
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practices on biomedical waste and its management among health care workers at a tertiary care hospital in Koppal, Karnataka, India

Abstract: Background: Biomedical waste carries a higher potential for infection and injury than any other type of waste. Inadequate and inappropriate handling of such waste may have serious public health consequences and a significant impact on the environment. Health care workers are the key workers in the management of biomedical waste and their inadequate knowledge, unfavorable attitude and poor practices are dangerous for their own health and those in the society. The objective of the present study was to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
3
7
0
Order By: Relevance
“…The findings are also parallel with many studies conducted among nurses/healthcare providers. For instance, Mane et al, (2016) detected that majority of the nurses were unaware about the risks linked with biomedical waste which comply to the findings of Sharma et al, (2013) who showed a lack of knowledge and awareness towards BMW among the participants. Similarly, Rajput et al, (2016) reported, most nurses did not know the exact number of color-coded containers needed for biomedical waste management.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The findings are also parallel with many studies conducted among nurses/healthcare providers. For instance, Mane et al, (2016) detected that majority of the nurses were unaware about the risks linked with biomedical waste which comply to the findings of Sharma et al, (2013) who showed a lack of knowledge and awareness towards BMW among the participants. Similarly, Rajput et al, (2016) reported, most nurses did not know the exact number of color-coded containers needed for biomedical waste management.…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, attention should be directed toward teaching and training nursing students and nurses for BMWM. Many studies pointed to the obligation of providing regular educational intervention and awareness or all health care personnel as a mean strategy for practical BMWM (Rao et al, 2018;Mane et al, 2016;Mathur, 2011Mathur, , 2012. Training could inspire motivation and change in mindset of all the healthcare personnel, specifically those in the junior level.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, hepatitis B virus vaccination was low (30.7%) as the level of occupational exposure among HCPs is high. It is extremely low compared to 85.8% and 95% studies conducted in India and Iran, respectively [ 13 , 36 ]. Unavailability and cost of the vaccine could be the possible causes for low vaccination status of HCPs in the current study.…”
Section: Discussionmentioning
confidence: 84%
“…Generation and disposal of BMWs have become an emerging problem worldwide [ 8 ]. It has become a major cause of concern for HCFs and the environment [ 12 , 13 ]. According to the World Health Organization report, 10–25% of the BMW was estimated to be hazardous [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation